Effect of high salt concentrations on the stability of immobilized lipases: Dramatic deleterious effects of phosphate anions. (November 2017) - Zaak, Hadjer; Fernandez-Lopez, Laura; Velasco-Lozano, Susana; Alcaraz-Fructuoso, Maria Teresa; Sassi, Mohamed; Lopez-Gallego, Fernando; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: Several enzymes were immobilized on octyl-glyoxyl supports. 4 M sodium phosphate readily inactivated the enzymes while the enzymes kept the activity in 6 M NaCl. 6 M NaCl has positive or negative effects on thermostability depending on the enzyme. 100 mM sodium phosphate presented moderate destabilizing effects in immobilized enzymes but not on all free enzymes. Fluorescence spectrum suggested a massive structural change produced by sodium phosphate. Abstract: We have analyzed the effects of the buffer nature on the stability of immobilized lipases. Commercial phospholipase Lecitase Ultra (LU), lipase B from Candida antarctica (CALB) and lipase from Thermomyces lanuginosus (TLL) have been immobilized on octyl-glyoxyl agarose beads. The enzymes were readily inactivated using 4 M sodium phosphate but 6 M NaCl did not inactivate them. Using 2 M of sodium phosphate, the inactivation of the 3 immobilized enzymes still was very significant even at 25 °C but at lower rate than with higher phosphate concentration. Thermal stress inactivations of the immobilized enzymes revealed that even 100 mM sodium phosphate produced a significant decrease in enzyme stability; this effect was less pronounced for Lecitase but dramatic for CALB. While 6 M NaCl presented slightly positive (LU) or negative (TLL) effects on their thermal stabilities of, CALB was thermally stabilized under the same conditions. Results were very different using free enymes. Fluorescence spectroscopy revealed dramatic structural rearrangements of the immobilized enzymes in the presence of high phosphate concentration. From these results, the use of sodium phosphate does not seem to be recommended for studies on thermal stability of lipases, although this should be verified for each enzyme and immobilized preparation.